The Disease Modification Conundrum in Parkinson’s Disease: Failures and Hopes - Mari, Zoltan; Mestre, Tiago A. (Frontiers in Aging Neuroscience, 2022)
In the last half century Parkinson disease (PD) has played a historical role in demonstrating our ability to translate preclinical scientific advances in pathology and pharmacology into highly effective clinical therapies. Yet, as highly efficacious symptomatic treatment were successfully developed and adopted in clinical practice, PD remained a progressive disease without a cure. In contrast with the spectacular success story of symptomatic therapies, the lack of translation of disease modifying interventions effective in preclinical models into clinical success continued to grow more frustrating, especially in the past 2 decades. The ability to stop, prevent, or mitigate progression in PD remains the “holy grail” in PD science at this time, as we yet to have a robust consensus to declare any intervention tested so far to accomplish that goal. The large number of high-quality disease-modifying clinical trials of the past 2 decades and our growing knowledge of PD, as well as the rapidly advancing related technology and clinical sciences in a broader sense should enable us with a deeper understanding of why we have failed before and what we need to do to improve our future outcomes.